Bioatividade de grãos de cafés oriundos de frutos imaturos e efeito sobre o metabolismo energético de camundongos - Gandra, Fernanda Paola de Pádua (2016)
In order to eliminate defective grains from the internal market, there is a need alternative proposals more attractive to coffee producers. The objective of this study was to evaluate the chemical composition and biodiversity of grains originated from immature fruits (green defect), as well as the effect of raw grains over the energetic metabolism of obese and eutrophic mice. Grains harvested in the cherry (mature) and green (immature) stages were used. For the evaluation of biodiversity of the high molecular weight material, the grains were roasted and fractioned in ethanol. We evaluated the centesimal composition, content of caffeine, total phenolic compounds, 5-ACQ, and antioxidant activities (DPPH-IC50). For the in vivo trial, the animals were divided into four groups: Eutrophic – fed a standard diet AIN-93; Eutrophic coffee – fed a standard diet AIN-93 + 1.0% of green defects; Obese – fed a diet rich in fat to induce obesity; Obese coffee – fed a diet rich in fat to induce obesity + 1.6% of green defect. Blood, white (epididymis and subcutaneous) and brown fat tissue, liver and gastrocnemious muscle were collected and weighed. The biochemical parameters were dosed in serum, and the contents of total lipids, triacylglycerol and cholesterol were dosed in the liver. After 8 weeks of treatment, the animals were submitted to the measuring of oxygen consumption. For evaluating the antioxidant activity in vivo, the levels of hydroperoxides, MDA, SOD and catalase in the fat tissue and liver were dosed. The contents of carbohydrates, lipids and macrominerals did not differ between the two analyzed samples. The defective grains presented considerable amounts of bioactive compounds and antioxidant activity in vitro. The green defect grains were capable of increasing the energy expense and reducing the fat mass, as well as the increase in ponderal weight of the obese animals. The in vivo antioxidant activity of the grains was proven by the increase of the activity of enzyme catalase in the fat tissue of the eutrophic animals. To evaluate the bioactivity of the high molecular weight material (HMWM) of the roasted grains, a characterization regarding the contents of sugars and glycolytic bonds, proteins, melanoidins, 5-ACQ and caffeine (HMWM fractions) was performed, and the antioxidant activity (DPPH-IC 50) was evaluated. The high molecular weight material (HMWM) of the green defect presented chemical composition similar to the HMWM of the coffee and expressive antioxidant capacity.